Performance And Emission Of Coated Porous Medium Burner With Cogeneration - Ismail, Ahmad Kamal (2016)
Global warming has led to the change of world climate. The increased volumes of carbon dioxide and other greenhouse gases released by the burning of fossil fuels have been identified as among the primary contributor to this issue. Although the cost and source of the hydrocarbon (HC) fuels are fluctuating, it has been widely used. Furthermore, the used of HC fuels for domestic application such as in conventional gas burner relates to long term effect on health of the user. An experimental investigation was conducted to explore the alternative way of using HC fuel with improved method of combustion. In this thesis, the application of porous medium burner for domestic application has been studied. Further enhancement has been done on the burner by enabling cogeneration system. This system utilized Thermoelectric (TE) cells to generate electricity from portable porous medium burner. Alumina ceramic PM foam is used during the experiment. Combustion was controlled during the experiment by using the equivalence ratio of in between 0.8 to 1.3. The TE cells were attached to burner wall to absorb heat. The TE cells were connected to TE charger system to manage power output and to charge a mobile phone with a lithium-ion battery. The flame temperature increased with the amount of supplied fuel for the given equivalence ratios. Results show that the PM burner can be used for heating and cell phone charging. The decreasing trend was observed in CO and undiluted CO emission as fuel increased. The experimental result shows similarities with the trends in previous works. NOx emissions were in the acceptable range. It is found that surface temperature value of plain alumina substrate was 675.7 ºC from experiment and 710 ºC from CFD simulation with 4.8% different. While the amount of NOx recorded by experiment was at 5 ppm and the results produced from CFD was at 7.05 ppm with 30% different. The CO value from CFD was in the acceptable range. Further investigation on the effect of Silicon Carbide (SiC-), Nickel (Ni-), and Chromium (Cr-) based coating to performance of porous medium burner are evaluated. A dip-coating technique was used to coat SiC-, Ni-, and Cr- powders on a pre-sintered porous Al2O3 substrate. The results show a significant improvement in surface flame temperature and combustion emissions over the plain Al2O3 substrate. The heat capacity of SiC coating materials contributed to better heat released when used with plain Al2O3 substrate. The highest recorded surface flame temperature at fixed flow rate was 750 ºC for SiC-coated, 741 ºC for Cr-coated, 739 ºC for Nicoated and plain substrate registered a temperature of only 634 ºC. An 18% increase in flame temperature was recorded for SiC-coated substrate when compared to the plain substrate. Moreover, coated substrate reduced emissions of CO, undiluted CO and NOx. It was also found that, SiC-coated substrate reported best overall power output generated when compared to the plain substrate. The flame temperatures produced due to coating is predicted by CFD simulation shows 3.5 % to 6.1 % different as compared to experimental results with SiC coated. It also maintained the highest flame temperature obtained from CFD. The CO and NOx emission have also been predicted from the CFD with acceptable range.